2016
DOI: 10.1021/acs.iecr.6b02029
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Duct-Vented Explosion of Hydrogen–Air Mixtures in a Wide Range of Equivalence Ratio

Abstract: A relief duct is often used for indoor vented enclosures to discharge unburnt and burnt gas mixtures to outdoors, but its use can significantly affect pressure relief and flame behavior. In the current paper, duct-vented explosions of hydrogen−air mixtures with equivalence ratios ranging from 0.8 to 4.0 were experimentally investigated in a small cylindrical vessel with a 50-cmlong relief duct. Different from "coherent deflagration" as previously reported, the maximum pressure rise rate in the duct is always l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…It was found that explosion overpressure increased with an increase in hydrogen concentration. Vented explosion of hydrogen air mixtures through a 0.5-m-long duct was investigated and it was found that the use of the relief duct significantly increased the explosion overpressure compared with the cases without the duct for hydrogen concentration ranging from lean to rich [25]. The experiments on explosion venting of hydrogen-air mixtures from a 1.5-m-long duct to a vented cylindrical vessel showed that maximum reduced overpressure first increased and then decreased with an increase in hydrogen concentration [26].…”
Section: Ponizy and Leyermentioning
confidence: 99%
See 4 more Smart Citations
“…It was found that explosion overpressure increased with an increase in hydrogen concentration. Vented explosion of hydrogen air mixtures through a 0.5-m-long duct was investigated and it was found that the use of the relief duct significantly increased the explosion overpressure compared with the cases without the duct for hydrogen concentration ranging from lean to rich [25]. The experiments on explosion venting of hydrogen-air mixtures from a 1.5-m-long duct to a vented cylindrical vessel showed that maximum reduced overpressure first increased and then decreased with an increase in hydrogen concentration [26].…”
Section: Ponizy and Leyermentioning
confidence: 99%
“…Apart from the previous investigations on duct-vented explosion of hydrogen-air mixtures [21,24,25], one of the most important issue has not been studied yet: how does the length of relief duct affect explosion venting? Because in the previous research [21,24,25], relief ducts with fixed length were used.…”
Section: Ponizy and Leyermentioning
confidence: 99%
See 3 more Smart Citations